Opportunities for up to date treatment of the colorectal cancer - Yovtchev, Yovtcho (Radiology and oncology (Ljubljana), 2001)
Background. Up to now the basic methods in the treatment of colorectal cancer are surgery, chemo- and radiotherapy. Throughout current years new methods were developed and successfully used in oncology; they consist of application of specific antibodies, the antibody driven enzyme pro-drug treatment, the application of radioimmunoconjugates and the radioimmunoguided surgery. Conclusions. With the applied methods for the treatment of colorectal cancer we prolong a disease-free surviving period, reduce subjective complaints and decrease mortality.
Keywords: Antibodies, monoclonal; Antineoplastic agents; Colorectal neoplasms; danka; debelo črevo; karcinom; Radioimmunotherapy; rak (medicina); Therapy; zdravljenje